The resultant effects of Al-Numaniyah Ox-bow Lake’s geomorphological development and the utilization of its ground - Salman , Dr.Ayad A. Ali (Thi Qar Arts Journal, 2023)
The research dealt with the geomorphological development of Al-Numaniyah Ox-bow Lake’s, which was a former turning point and separated from the course of the Tigris River near the city of Al-Numaniyah in central Iraq. It became clear from the research the role of natural characteristics in the formation and geomorphic development of the lake, and it was estimated that the lake was cut off from the Tigris naturally in 1884, and since that time the lake was subjected to atrophy and its area shrunk due to the impact of water and wind sedimentation, but human intervention contributed to changing the direction of development towards the expansion of its area in the period until it reached its current area (1.42) km 2, through its previous use as a quarry for the extraction of table salt, and its current use as a pool for draining water from neighboring agricultural lands. The interruption of the torsion from the river and its transformation into a lake had effects (geomorphic, hydrological, environmental, pedological) in terms of weathering, erosion and sedimentation processes, in addition to the variation in the characteristics of the lake water between summer and winter due to the effect of the variation of climate elements, agricultural seasons, quantities of drainage water and the percentage of groundwater recharge, and in general The high salinity of the water affected the salinity of the banks of the lake and the neighboring areas to the extent that it was known as (salt river) or (Al-Numaniyah Salt). The land uses of the lake and the surrounding land have changed as a quarry for salts or an agricultural wasteland, with the land cover changing towards an increasing number of land uses at the present time, and the research ended with some targeted suggestions.